Tecnologia de aplicação aérea e terrestre no controle da ferrugem alaranjada (Puccinia Kuehnni (W. KRÜGER) E.J. BUTLER) da cana-de-açúcar (Saccharum spp) - Alves, Thales Cassemiro (2016)
The application of phytosanitary products in the sugar and ethanol industry has usually targeted pest control. With the epidemic rise in orange rust in sugarcane, caused by fungus Puccinia kuehnii, applications of fungicides are now necessary to protect susceptible varieties. However, few studies have focused on the impacts of the application technology, especially regarding the aerial application and its effects on the plant physiology. This study investigated the different forms of application of fungicides in sugarcane variety SP81-3250 and their association with spray deposition, disease control, productivity, and plant physiology. Experimental units received two different applications of fungicides of the chemical groups strobilurin and triazole. Aerial applications were performed using two different volume rates (30 and 40 L ha-1) and spray bar nozzles in three different angles (135°, 0° and 90 ° to the flight line). The 90° angle, the aerial standard used at sugar factory Usina Vale do Tijuco, was assessed at the second application only. Ground applications were performed using rates of 200 L ha-1 and flat fan spray nozzles with air induction (AI11004-VS). This procedure, used as the ground standard in the sugar factory, was measured in the first application only. The research was divided into two parts. In the first part, spray deposition in the upper canopy and losses to soil were assessed using tracer Brilliant Blue for absorbance spectrophotometry. It addition, sugarcane biometrics was measured, droplet spectrum was analyzed through the assessment of impacts on water sensitive paper, and disease severity on leaves was quantified using a digital image analysis software program. In the second part, gas exchange was assessed using gas analyzer IRGA, and the amount of chlorophyll a and b was measured using a chlorophyll meter. Data were analyzed using Student’s t test for independent samples, with significance set at 0.05. Aerial application with lower volume rates (30 L ha-1) provided greater deposition of fungicide and greater productivity than the application with 40 L ha-1. The angle of the spray nozzles facing backwards in the plane bar, so as to produce larger droplets, did not influence the application result, and thus, proved to be a viable alternative to reduce drift. Aerial applications with fine and medium droplets provided higher spray deposition on sugarcane leaves and less loss to soil compared to ground applications with extremely coarse droplets. Fungicide application generated increases in productivity of over 20 t ha-1, regardless of application form, reaching 40 t ha-1 with aerial applications. Aerial application provided generally better photosynthetic rates compared to ground application, with better photosynthesis performance and higher concentration of chlorophyll a and b in the leaf blade compared to ground application. No differences were found in gas exchange across the air applications in different operating conditions for volume rates and angles of the spray bar nozzle.